Problematic Arrangements for Termination of Employment in the Job Creation Law - Gilang Ramadhan; Amalia Diamantina (Varia Justicia, 2020)
This study aims to identify the value of Pancasila justice related to labor in the Job Creation Law. The method used in this research is a normative juridical method through a statutory and conceptual approach. The legal materials used are the 1945 Constitution and Law Number 13 of 2003 concerning Labor (Labor Law) compared to the Omnibus Law, which also regulates Labor. The results showed that the issuance of the Job Creation Law caused many losses for workers/laborers in providing wages, eliminating the right to wages, severance pay, compensation for rights, and compensation for workers/laborers. In addition, there is a lost right in suing an employer if a worker does not receive a layoff because of serious mistakes. Finally, employers who do not include pension workers in the pension program cannot be prosecuted. Amendments to the Job Creation Law must be made considering that laws must be made based on Pancasila justice. In current conditions, workers' rights are being erased so that the Job Creation Law is considered to only favor employers.